The evolving role of liver transplantation for metastatic colorectal cancer: current perspectives and future directions - Bendersky, Victoria A.; Olaso, Danae G.; Schnickel, Gabriel T. (Frontiers in Surgery, 2025)
Liver transplantation is increasingly being explored as a treatment option for select patients with metastatic colorectal cancer (mCRC). Historically, transplantation for mCRC was abandoned due to poor long-term outcomes and high recurrence rates. However, recent advancements in patient selection, immunosuppressive strategies, and donor organ availability have led to a renewed interest in this approach. Studies have demonstrated that highly selected patients undergoing liver transplantation can achieve significantly improved survival rates compared to those receiving standard systemic therapies. The implementation of Model for End-Stage Liver Disease (MELD) exception points, improved donor preservation techniques such as machine perfusion, and the growing role of living donor liver transplantation have further supported its feasibility. As research continues, liver transplantation may emerge as a crucial component of a multidisciplinary strategy for treating colorectal liver metastases, offering a select group of patients a chance at prolonged survival and improved quality of life.